The role of occupational Aspergillus exposure in the development of diseases. (28th February 2019) - Sabino, Raquel; Veríssimo, Cristina; Viegas, Carla; Viegas, Susana; Brandão, João; Alves-Correia, Magna; Borrego, Luís-Miguel; Clemons, Karl V; Stevens, David A; Richardson, Malcolm
Abstract: Aspergillus spp. have a high nutritional versatility and good growth on a large variety of construction materials. They also colonize soil or food, but decaying vegetation is their primary ecological niche. Therefore, exposure to fungi may occur at home, during hospitalization, during specific leisure activities, or at the workplace. The development of Aspergillus infections depends on the interplay between host susceptibility and the organism. Environments with high counts of fungal elements (conidia, hyphal fragments and others), high levels of bioarerosols, and elevated concentrations of mycotoxins or other volatile organic compounds should be considered as potential hazards, since they may present a risk to the exposed person. Rural tasks as well as work related to wood and food industries, poultries, swineries, waste handling plants, and other occupational environments involving contaminated organic material are among the ones posing higher respiratory risks to the workers. This paper presents a review of several studies related to occupational and indoor exposure to Aspergillus, potential health effects related to that exposure, and associated exposure assessment procedures.